Private sector adaptive capacity to climate change impacts in the food system: food security implications for South Africa and Brazil - Pereira, L; Laura Pereira (2012)
Achieving food security under climate change is one of the biggest challenges of the 21st century. The challenge becomes even greater when contextualised within our current limited understanding of how the food system functions as a complex, adaptive socio-ecological system, with food security as one of its outcomes. Adding climate change into this already complex and uncertain mix creates a ‘wicked problem’ that must be solved through the development of adaptive food governance. The thesis has 4 key aims: 1. To move beyond an understanding of food security that is dependent solely on agricultural production, and therefore the reliance of future food security predictions on production data based on climate model inputs. 2. To ground the theoretical aspects of complex adaptive systems with empirical data from multi-level case studies. 3. To investigate the potential role of the private sector in food system futures. 4. To analyse food system dynamics across scales and levels. In order to realise these aims, a complex adaptive system (CAS) approach within the GECAFS food system framework is employed to multilevel case studies in South Africa and Brazil. Particular emphasis is placed on the role of the private sector and how these vital actors, comprising a powerful component of the global food system, can be mobilized towards building adaptive capacity for a more resilient food system. Critically, the private sector is often left out of academic discussions on adaptation, which tend to focus more on civil society and governmental capacity to adapt. This thesis provides novel insight into how the power of the private sector can be harnessed to build adaptive capacity. The findings of the thesis showed that applying CAS to issues of governance has three important implications: The first is that in a complex system, it is critical to maintain diversity. This can translate into appreciating a multiplicity of viewpoints in order to reflect a range of decision-making options. This finding makes the case for closer synergy between the public and private sectors around areas like product development and distribution that includes an emphasis on enhancing food security under climate change. In the developing country context, the inclusion of smallholders and local entrepreneurs is also vital for building adaptive capacity. In this sense, it is possible for business to help achieve development goals by developing the capacity of those most vulnerable to socio-economic and environmental shocks. Secondly, adapting to climate change and other environmental and economic pressures will require a shift in mind-set that embraces the uncertainty of the future: ‘managing for uncertainty rather than against it’. This entails a shift in governance mindset away from linear thinking to a decision-making paradigm that is more flexible to deal with unexpected shocks. The third implication for governance is the need to understand the complex interplay of multiple interlinking processes and drivers that function across many levels and sometimes have exponential positive feedbacks in the food system. Adaptive governance is an iterative process, but as more is learnt and information is retained in the system, the ideal is that the beneficial processes that lower inequality and increase food security will start to be reinforced over those that entrench the current inequality in the food system.